Enhancing FAPbI3 Perovskite Solar Cell Performance and Stability Through Bespoke Graphene Quantum Dots - Jin Kyoung Park; Yunmi Song; Hyong Joon Lee; Kyung Ho Kim; Jin Hyuck Heo; Sang Hyuk Im (EcoMat)
ABSTRACT A novel approach to enhancing the efficiency and long‐term stability of perovskite solar cells (PSCs) is presented through strategic interfacial modification using bespoke graphene quantum dots (GQDs). GQDs with controlled alkylamine chain lengths, such as butylamine (C4), octylamine (C8), and dodecylamine (C12), were customized to have the proper optical and electronic properties toward specific interfaces within the PSCs. The incorporation of C4‐GQDs significantly improved the energy level alignment and conductivity of the SnO2 electron transport layer (ETL), while C12‐GQDs effectively reduced trap density on the perovskite surface, leading to enhanced defect passivation. These modifications resulted in a substantial increase in power conversion efficiency of 24.41% in a unit cell and 18.91% in a mini‐module, respectively. Notably, the maximum power point tracked perovskite mini‐module retained 89% of its initial efficiency during 1000 h of continuous light soaking condition at 25°C under 35% relative humidity. This work highlights the potential of bespoke GQDs to advance both the performance and durability of PSCs, providing a scalable approach for future photovoltaic applications.